HIV-Infected Children Have Lower Frequencies of CD8+ Mucosal-Associated Invariant T (MAIT) Cells that Correlate with Innate, Th17 and Th22 Cell Subsets. - Alka Khaitan; Max Kilberg; Adam Kravietz; Tiina Ilmet; Cihan Tastan; Mussa Mwamzuka; Fatma Marshed; Mengling Liu; Aabid Ahmed; William Borkowsky; Derya Unutmaz (PLoS ONE, 2016)
Mucosal-associated invariant T cells (MAIT) are innate T cells restricted by major histocompatibility related molecule 1 (MR1) presenting riboflavin metabolite ligands derived from microbes. Specificity to riboflavin metabolites confers MAIT cells a broad array of host-protective activity against gram-negative and -positive bacteria, mycobacteria, and fungal pathogens. MAIT cells are present at low levels in the peripheral blood of neonates and gradually expand to relatively abundant levels during childhood. Despite no anti-viral activity, MAIT cells are depleted early and irreversibly in HIV infected adults. Such loss or impaired expansion of MAIT cells in HIV-positive children may render them more susceptible to common childhood illnesses and opportunistic infections. In this study we evaluated the frequency of MAIT cells in perinatally HIV-infected children, their response to antiretroviral treatment and their associations with HIV clinical status and related innate and adaptive immune cell subsets with potent antibacterial effector functions. We found HIV+ children between ages 3 to 18 years have significantly decreased CD8+ MAIT cell frequencies compared to uninfected healthy children. Remarkably, CD8 MAIT levels gradually increased with antiretroviral therapy, with greater recovery when treatment is initiated at a young age. Moreover, diminished CD8+ MAIT cell frequencies are associated with low CD4:CD8 ratios and elevated sCD14, suggesting a link with HIV disease progression. Last, CD8+ MAIT cell levels tightly correlate with other antibacterial and mucosa-protective immune subsets, namely, neutrophils, innate-like T cells, and Th17 and Th22 cells. Together these findings suggest that low frequencies of MAIT cells in HIV positive children are part of a concerted disruption to the innate and adaptive immune compartments specialized in sensing and responding to pathogenic or commensal bacteria.